Aktivitas Antibakteri beberapa Tanaman dari Famili Asteraceae terhadap Bakteri Mycobacterium tuberculosis - Annisa Dila Perwitasari; Lanny Mulqie; Umi Yuniarni (UNISBA Press, 2024)
Abstract. Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis bacteria where one of the keys to successful treatment is adherence. There have been many in vitro studies conducted from Asteraceae plants that can be used to treat tuberculosis in several countries. This study aims to determine Asteraceae plants that have antibacterial activity against the growth of bacteria that cause tuberculosis. The research was conducted using the Systematic Literature Review (SLR) method using the keywords